1992
DOI: 10.1300/j015v12n01_15
|View full text |Cite
|
Sign up to set email alerts
|

Differential Perceptions of Sexism

Abstract: Given the amount of discussion and debate surrounding issues relating to sexism, it is clear that individuals disagree over what particular aspects of life are approprialely labelled sexist. The present study was designed to assess the nature of disagreement among individuals about what constitutes sexism and to show that such disagreement can be detrimentalto the success of therapy. Sexism perceived in a series of hypothetical scenarios correlated positively with sexism experienced in one's own life. This sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Several studies showed, for example, that women are more likely than men to view the same behaviors as sexist and people lower in self-reported levels of sexism are more likely to conclude that specific behaviors are sexist (Blodorn, O’Brien, & Kordys, 2012; Inman & Baron, 1996; Smith, 1992; Swim et al, 2005). Although examining sexism inferences as a function of gender and attitudes describes who is more or less likely to infer sexism, these approaches do not fully account for why these people see more sexism in others’ behavior and they do not directly identify the psychological processes involved in reaching a conclusion of sexism.…”
Section: Sources Of Variability In Judgments Of Sexismmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed, for example, that women are more likely than men to view the same behaviors as sexist and people lower in self-reported levels of sexism are more likely to conclude that specific behaviors are sexist (Blodorn, O’Brien, & Kordys, 2012; Inman & Baron, 1996; Smith, 1992; Swim et al, 2005). Although examining sexism inferences as a function of gender and attitudes describes who is more or less likely to infer sexism, these approaches do not fully account for why these people see more sexism in others’ behavior and they do not directly identify the psychological processes involved in reaching a conclusion of sexism.…”
Section: Sources Of Variability In Judgments Of Sexismmentioning
confidence: 99%
“…The scientific literature, which is replete with examples of disagreements about the extent to which any given behavior is sexist or innocuous, adds to the confusion (Brant, Mynatt, & Doherty, 1999; Smith, 1992; Swim, Mallett, Russo-Devosa, & Stangor, 2005; Trenholm & Manciallas, 1978). Indeed, the ambiguities surrounding “sexism” are reminiscent of the ambiguity surrounding the definition of “obscenity” when Supreme Court Justice Potter Stewart famously stated, “ I know it when I see it ....” regarding potential obscenity in Louis Malle’s film The Lovers (Jacobellis v. Ohio, 1964).…”
mentioning
confidence: 99%
“…Firstly, the extent of the emotional response and the emotion regulation strategy employed may differ between genders in response to sexism. This may be due to experiences of sexism since females are more likely to be targets of sexist acts compared to their male counterparts in their everyday lives [ 88 ]. In addition, previous findings from [ 30 ] have suggested that males may be more efficient in terms of neural activity during negative emotion regulation as less prefrontal activity during regulation was observed in males.…”
Section: Discussionmentioning
confidence: 99%